Non‐random species loss in bacterial communities reduces antifungal volatile production. Issue 8 (1st August 2015) - Hol, W. H. Gera; Garbeva, Paolina; Hordijk, Cornelis; Hundscheid, Maria P. J.; Gunnewiek, Paulien J. A. Klein; Agtmaal, Maaike; Kuramae, Eiko E.; de Boer, Wietse
Abstract : The contribution of low‐abundance microbial species to soil ecosystems is easily overlooked because there is considerable overlap between metabolic abilities (functional redundancy) of dominant and subordinate microbial species. Here we studied how loss of less abundant soil bacteria affected the production of antifungal volatiles, an important factor in the natural control of soil‐borne pathogenic fungi. We provide novel empirical evidence that the loss of soil bacterial species leads to a decline in the production of volatiles that suppress root pathogens. By using dilution‐to‐extinction for seven different soils we created bacterial communities with a decreasing number of species and grew them under carbon‐limited conditions. Communities with high bacterial species richness produced volatiles that strongly reduced the hyphal growth of the pathogen Fusarium oxysporum . For most soil origins loss of bacterial species resulted in loss of antifungal volatile production. Analysis of the volatiles revealed that several known antifungal compounds were only produced in the more diverse bacterial communities. Our results suggest that less abundant bacterial species play an important role in antifungal volatile production by soil bacterial communities and, consequently, in the natural suppression of soil‐borne pathogens.